2021
DOI: 10.1101/2021.07.15.452449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterogeneity in the transcriptional response of the human pathogen Aspergillus fumigatus to the antifungal agent caspofungin

Abstract: Aspergillus fumigatus is the main causative agent of invasive pulmonary aspergillosis (IPA), a severe disease that affects immunosuppressed patients worldwide. The fungistatic drug caspofungin is the second line therapy against IPA but has increasingly been used against clinical strains that are resistant to azoles, the first line antifungal therapy. In high concentrations, caspofungin induces a tolerance phenotype with partial reestablishment of fungal growth called caspofungin paradoxical effect (CPE), resu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…CrzA regulates the activation of several stress responses and cell wall modifications (21, 19). Interestingly, crzA deletion in the clinical strain Af293 results in CPE loss (22, Figure 2C ), while crzA deletion in the CEA17 background is CPE + (23, 19, Figure 2C ), demonstrating intra-species differences or CPE heterogeneity. Differently from Δ crzA CEA17 mutant, the Δ crzA Af293 mutant cannot activate cell wall remodeling genes upon CAS exposure, affecting its CPE (23).…”
Section: Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…CrzA regulates the activation of several stress responses and cell wall modifications (21, 19). Interestingly, crzA deletion in the clinical strain Af293 results in CPE loss (22, Figure 2C ), while crzA deletion in the CEA17 background is CPE + (23, 19, Figure 2C ), demonstrating intra-species differences or CPE heterogeneity. Differently from Δ crzA CEA17 mutant, the Δ crzA Af293 mutant cannot activate cell wall remodeling genes upon CAS exposure, affecting its CPE (23).…”
Section: Observationmentioning
confidence: 99%
“…Interestingly, crzA deletion in the clinical strain Af293 results in CPE loss (22, Figure 2C ), while crzA deletion in the CEA17 background is CPE + (23, 19, Figure 2C ), demonstrating intra-species differences or CPE heterogeneity. Differently from Δ crzA CEA17 mutant, the Δ crzA Af293 mutant cannot activate cell wall remodeling genes upon CAS exposure, affecting its CPE (23). The CGIs for Δ crzA CEA17 and Δ crzA Af293 mutant strains are 100 and 0 %, respectively, when grown on MM+8 µg/ml independently if the conidia are derived from MM or MM+8 µg/ml ( Figure 2D, Supplementary Table S3 at 10.6084/m9.figshare.19178888 ).…”
Section: Observationmentioning
confidence: 99%
“…Variation in non-coding regions can also contribute to phenotypic variation, including gene expression variation between and within species (Caroll, 2005;Hill et al, 2020). We have previously demonstrated that non-coding regions between two A. fumigatus reference strains, Af293 and A1163 (Brown et al, 2022;Colabardini et al, 2022), as well as between A. fumigatus and its non-pathogenic close relatives are highly variable (Brown et al, 2022). For example, we found that 418 A. fumigatus genes exhibit a different rate of evolution in their non-coding regions (relative to non-pathogenic close relatives), including the non-coding regions of 25 genes that are known genetic determinants of A. fumigatus virulence.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, ZfpA null hyphae have reduced branching, septation, and cell wall chitin. In addition to its role in hyphal development, ZfpA has been implicated in A. fumigatus response to stressors such as high calcium and the antifungals voriconazole and caspofungin [1518]. However, whether ZfpA affects fungal growth and susceptibility to host immunity and antifungal treatment during infection remains unclear.…”
Section: Introductionmentioning
confidence: 99%